Central executive – unitary component or different modules? - Vranić, Andrea (Array, 2006)
In the working memory model attentional operations are attributed to the central executive component. CE is a strategic and a resource-demanding component serving in orienting attention, organizing information, initiating and guiding search at retrieval. CE is the least studied component of the WM model ; its unitary or modular nature still being debated. In memory tasks tapping strategic processes dividing attention should have a decremental effect. Memory decrement speaks of limitations of the central executive in terms of attentional resources and is larger with the secondary task requiring more attention. If memory decrement is found to be different when memory task is combined with the same-domain vs. different-domain secondary task, results would point to a modular nature of central executive. Therefore, a divided attention paradigm was used where participants performed an auditory word recall task and a visually presented secondary task. Secondary task was a same- or different-domain (verbal vs. numerical).